Commentary: Bringing together lived experience, clinical and research expertise – a commentary on the May 2022 debate (should CAMH professionals be diagnosing personality disorder in adolescence?). Issue 3 (22nd July 2022) - Hartley, Samantha; Baker, Charley; Birtwhistle, Michael; Burgess, Jennifer L.; Chatburn, Eleanor; Cobbaert, Laurence; Howley, Maddie; Huggett, Charlotte; MacKenzie‐Nash, Charlie; Newton, Alice; Parry, Sarah; Smith, Jee; et al.
Abstract : Background: There is a wealth of evidence to suggest that the Borderline Personality Disorder (BPD, or similar Emotionally Unstable Personality Disorder, EUPD) construct is harmful. We provide a commentary on the ideas expressed in the May Debate issue, highlighting both concerns and alternatives. Method: We bring together lived experience, clinical and research expertise. This commentary was written collaboratively drawing on all these sources of evidence. Results: We outline evidence that the BPD construct is invalid, harmful, not necessary for effective treatment and a potential block to the development and evaluation of alternatives. Conclusions: We ask readers to consider these concerns, perspectives and ideas.